2023
DOI: 10.31219/osf.io/mvz8t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Application of Social Exchange Theory by Entrepreneurs Leading Small Businesses in Appalachia

Abstract: Entrepreneurs are the backbone of the U.S. economy and their small businesses represent the primary job source forAmerican workers. Research exists on small business at a national and an international scale but a limited amountof region specific information exists in the literature. The purpose of the research is to explore the relationshipbetween social capital and the failure or success of entrepreneurs who own businesses in Beckley, West Virginia, asmall Appalachian town. The theoretical framework for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Using social exchange theory as a theoretical framework, [26] conducted a study to explore the relationship between social capital and the failure or success of entrepreneurs who own businesses in Beckley, West Virginia. The study found out that application of social exchanges by entrepreneurs increased the longevity of small businesses.…”
Section: Assumptions Of Social Exchange Theorymentioning
confidence: 99%
“…Using social exchange theory as a theoretical framework, [26] conducted a study to explore the relationship between social capital and the failure or success of entrepreneurs who own businesses in Beckley, West Virginia. The study found out that application of social exchanges by entrepreneurs increased the longevity of small businesses.…”
Section: Assumptions Of Social Exchange Theorymentioning
confidence: 99%